THE FUNDAMENTAL AND SOCIAL RIGHTS TO HOUSING AND ITS REFLECTIONS IN THE COVID-19 PANDEMIC SCENARIO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The project aims to analyze the fundamental and social right to housing and its consequences in the scenario of the COVID-19 pandemic for groups that are in a state of greater vulnerability. Guarantee the right to housing, provided for in art. 6 of the Federal Constitution of 1988, in the pandemic scenario that we are experiencing, it was essential, as one of the main ways to control the spread of the virus and guarantee public health was social isolation and staying at home. Faced with the urgency of maintaining decent housing for the most vulnerable groups and of resolving conflicts such as property rights and the right to housing, legal operators and legislators were required to act ostensibly to provide greater legal protection to this very elementary right.The methodology was based on a bibliographic review and a study of jurisprudence